Schumpeter and Steindl on Maturity and Growth in Capitalism - Bloch, Harry; Finch, J. (University of Ballarat, 2006)
Joseph Schumpeter and Josef Steindl provide distinctive contributions to the analysis of growth and development under capitalism. They each relate growth outcomes to the dynamics of competition. They also each analyse the evolution of competition and use this analysis to determine the growth prospects of mature capitalism. Both reach pessimistic conclusions, although for different reasons. This paper critically examines the analysis of each author and makes suggestions for building on their work to provide a more complete theory of economic growth and transformation, which can be used to assess current and future growth prospects for advanced capitalist economies. Scientific analysis is not simply a logically consistent process that starts with some primitive notions and then adds to the stock in some straight-line fashion. It is not simply progressive discovery of some objective reality - as is, for example, discovery in the basin of the Congo. Rather it is an incessant struggle with creations of our own and our predecessors' minds and it 'progresses', if at all, in a criss-cross fashion, not as logic, but as the impact of new ideas or observations or needs, and also as the bents and temperaments of new men, dictate. (Schumpeter, 1954, p.41)